If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 9 + 7x = 2 + x + 7 Reorder the terms: 9 + -6x + 7x = 2 + x + 7 Combine like terms: -6x + 7x = 1x 9 + 1x = 2 + x + 7 Reorder the terms: 9 + 1x = 2 + 7 + x Combine like terms: 2 + 7 = 9 9 + 1x = 9 + x Add '-9' to each side of the equation. 9 + -9 + 1x = 9 + -9 + x Combine like terms: 9 + -9 = 0 0 + 1x = 9 + -9 + x 1x = 9 + -9 + x Combine like terms: 9 + -9 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| 5(4x-1)=5(6x-3) | | 7=k+(-3) | | 3x^2+4x^2=400 | | 6(5+8n)-2(n-6)=42 | | -8b-4=8-5b-5b | | -(3x-5)=6(2x+5) | | 8z+3=7z+3 | | 1y-(8-1y)=32 | | x^2-15=106 | | 24-3n=-6(6n-4) | | 6+6r=36 | | 7+19x=28+12x | | Y=15-4(-3) | | 1-a+8=-6a-11 | | -2[-c-20]=-2c-20 | | -15+2x-7x=-10+15x | | 4(5y-1)=6(4y-4) | | =7-(5x+2) | | 8x+17=6x-13 | | 10t+2=6t+6 | | (4x+8)(6-9)=0 | | 6x+3y=6x | | 2[2x-10]=4[x-10] | | 2.66666667=-72 | | 6+49x^2=10 | | 15+7g=13+8g+7 | | 5(5q+5)=6(6q-5) | | 3x-12=-9x | | 2b-5=7b+1 | | 24x+18-14=-18x+27 | | -4x-56=-4x+6 | | 4[a-6]=8a-[4a+24] |